The Use of Flipped Classroom to Improve Students Writing Skill Using WhatsApp Group - Wahyu Restu Indayani; Yudhi Arifani; Ulfatul Ma’rifah (Jetlal, 2022)
The rapid advancement of technology has piqued the interest of English Language Teaching (ELT) researchers in investigate the effectiveness of flipped classrooms. The subject of this study is two classes of tenth grade students from SMA Muhammadiyah 10 GKB. A quasi-experimental design was used in both classes to determine the significance of the difference between the flipped classroom via WhatsApp group class and the non-flipped class. In this study, the improvement of students' writing skills during treatments is measured. The experimental group (N=23) was given recount text video material and a task from a WhatsApp group outside of class, while the material was reinforced in class. The control group (N=23) was taught using non-flip teaching, in which learning material is mostly delivered in class and additional exercise is given outside of class. The initial and final tests include a pre- and post-test. The results show that the significance value (2-tailed) was 0.010 (p<0.05). This means that a flipped classroom using a WhatsApp group improves students' writing skills significantly. It is suggested that advanced researchers use another field of study to implement this flipped classroom. The findings of this study will help students improve not only their writing skills, but also their other skills. As for the teacher, the flipped classroom has shown a positive impact on students, providing an opportunity for teachers to implement this model.